2016
DOI: 10.1371/journal.pone.0159305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monotherapy with Darunavir/Ritonavir on Viral Load in Seminal Fluid, and Quality Parameters of Semen in HIV-1-Positive Patients

Abstract: Patients with human immunodeficiency virus type 1 (HIV-1) who receive antiretroviral therapy (ART) often achieve increased survival and improved quality of life. In this respect, monotherapy with darunavir/ritonavir (mDRV/r) can be a useful treatment strategy. This prospective study analyses the effect of mDRV/r on sperm quality and viral load in a group of 28 patients who had previously been given conventional ART and who had recorded a viral load <20 copies/mL for at least six months. These patients were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
2
10
1
Order By: Relevance
“…The semen quality of patients who are positive for HIV-1 and receiving treatment with ART is known to be impaired [ 4 , 5 ]. A similar decrease has been observed in HIV-1 patients who continue treatment with monotherapy with darunavir/ritonavir (mDRV/r) (800/100mg) [ 6 ].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…The semen quality of patients who are positive for HIV-1 and receiving treatment with ART is known to be impaired [ 4 , 5 ]. A similar decrease has been observed in HIV-1 patients who continue treatment with monotherapy with darunavir/ritonavir (mDRV/r) (800/100mg) [ 6 ].…”
Section: Introductionsupporting
confidence: 60%
“…The results for viral load and semen quality of these 20 patients, after treatment with mDRV/C for 24 weeks, were compared with those obtained in a previous study performed in 21 patients who after receiving at least 24 weeks of ART, were given mDRV/r for 48 weeks [ 6 ]. Of the 20 patients with mDRV/C, five had previously participated in this previous study of mDRV/r [ 6 ] ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both compounds exhibited a good docking score, an initial investigation of both of them showed that darunavir but not ubrogepant had an history as an antiviral compound [17]; therefore, selected for further computational studies. First, the preference of binding was determined using MMPBSA [13] free energy values obtained from 2019-nCoV-RBD in complex with darunavir and those obtained from the candidate bound to 2019-nCoV-RBD/ACE-2.…”
Section: -Ncov-rbd/ace-2 Complex High Affinity Bindermentioning
confidence: 99%
“…4 Similarly, seminal positive result for HIV RNA was found despite a negative result for HIV RNA was found in blood. 5 Gene sequencing of proviral protease and DNA envelope genes has shown different variants in seminal plasma and blood. 1 The presence of HIV in seminal plasma seems to depend on various factors that may influence its presence in this compartment, even when it is undetectable in blood.…”
Section: Introductionmentioning
confidence: 99%